Oral health behavior and oral hygiene habits of elderly population in Podgorica, Montenegro - Popović Zorica; Đuričković Mirjana (Serbian Medical Society - Dental Section, Belgrade, 2019)
Introduction an increase in the number of elderly users of dental services is expected in bubbling. The aim of the study was to examine the oral health behaviour and oral hygiene habits of the elderly population in Podgorica, Montenegro. Materials and methods the study used a 21 closed-end question questionnaire, prepared in accordance with the recommendations of the World Health Organization. Using standard statistical methods, ch2 test was performed (p = 0.05). Results the average age of subjects was 71 ± 6.35. 40.0% of population was edentulous; 81.90% had some kind of dentures; last visit to the dentist was less than a year ago in 25.7% and more than five years ago in 27.6%. Higher educated population had regular dental check-ups (ch2 = 47.178; p < 0.001). The reason for dental visit was most commonly pain or other mouth discomfort, teeth or dentures in 59.0%. 33.3% of examined population reported fear of dental interventions as the reason for the lack of dental care. 16.2% reported high cost of dental services as reason for avoiding dentist. 41.0% of population used tobacco products and 21.0% alcoholic beverages. Les than half of population (40.0%) had regular dentist. 41% of population brushed teeth and dentures three times a day, oral hygiene AIDS use was noted in 35.6% while 50% used denture-cleaning tablets. Conclusion Oral health behaviour and oral hygiene habits of the elderly in Podgorica are not satisfactory. Since elderly are mostly in need of prosthetic treatment it is important to improve dental-prosthetic care in the state health care system.